EFEKTIVITAS KUALITAS PELAYANAN KESEHATAN MASYARAKAT (JIANA ( Jurnal Ilmu Administrasi Negara ), 2014)
The purpose of this study is todetermine the effectiveness of the quality of public health services at the Public Health Centerin Palembang with service indicators; tangibles, reliability , responsiveness, assurance andempathy. The research methodology based quantitative descriptive survey. The unit of analysis isa clinic in Palembang. Samples use purposive sampling method : 2 main public health centers,four public health centers in a center of Palembang city, and 2 public health centers in suburb ofPalembang. Samples are 721 people. Data collection techniques using a questionnaire with fiveresponse categories in Likert Scale . The results showed that the quality of public health servicesin Palembang as perceived by the respondents is lower than what is expected of respondents(patients). The model used to improve the quality of health care in public health centers arestarting strengthen the chain of variable reliability, followed by empathy, responsiveness,assurance and tangibles.Keywords: quality of service, reliability, assurance, empathy, responsiveness